Clinical utility and prospective of TMS–EEG. Issue 5 (May 2019) - Tremblay, Sara; Rogasch, Nigel C.; Premoli, Isabella; Blumberger, Daniel M.; Casarotto, Silvia; Chen, Robert; Di Lazzaro, Vincenzo; Farzan, Faranak; Ferrarelli, Fabio; Fitzgerald, Paul B.; Hui, Jeanette; Ilmoniemi, Risto J.; et al.
Highlights: An overview of TMS-EEG methodology and neurophysiological derivations. A comprehensive review of TMS-EEG as a clinical tool to study healthy and disease brain states. A discussion of current challenges in the field of TMS-EEG and recommendations for future studies. Abstract: Concurrent transcranial magnetic stimulation and electroencephalography (TMS–EEG) has emerged as a powerful tool to non-invasively probe brain circuits in humans, allowing for the assessment of several cortical properties such as excitability and connectivity. Over the past decade, this technique has been applied to various clinical populations, enabling the characterization and development of potential TMS–EEG predictors and markers of treatments and of the pathophysiology of brain disorders. The objective of this article is to present a comprehensive review of studies that have used TMS–EEG in clinical populations and to discuss potential clinical applications. To provide a technical and theoretical framework, we first give an overview of TMS–EEG methodology and discuss the current state of knowledge regarding the use of TMS–EEG to assess excitability, inhibition, plasticity and connectivity following neuromodulatory techniques in the healthy brain. We then review the insights afforded by TMS–EEG into the pathophysiology and predictors of treatment response in psychiatric and neurological conditions, before presenting recommendations for how to address some of the salient challenges faced in clinical TMS–EEG research. Finally, we conclude by presenting future directions in line with the tremendous potential of TMS–EEG as a clinical tool.